Silicon Uptake and Localisation in Date Palm (Phoenix dactylifera) – A Unique Association With Sclerenchyma - Bokor, Boris; Soukup, Milan; Vaculík, Marek; Vd’ačný, Peter; Weidinger, Marieluise; Lichtscheidl, Irene; Vávrová, Silvia; Šoltys, Katarína; Sonah, Humira; Deshmukh, Rupesh; Bélanger, Richard R.; White, Philip J.; et al. (Frontiers in Plant Science, 2019)
Date palm (Phoenix dactylifera) can accumulate as much as 1% silicon (Si), but not much is known about the mechanisms inherent to this process. Here we investigated in detail the uptake, accumulation and distribution of Si in date palms, and the phylogeny of Si transporter genes in plants. We characterised the PdNIP2 transporter following heterologous expression in Xenopus oocytes and used qPCR to determine the relative expression of Si transporter genes. Silicon accumulation and distribution was investigated by light microscopy, scanning electron microscopy coupled with X-ray microanalysis and Raman microspectroscopy. We proved that PdNIP2-1 codes for a functional Si-permeable protein and demonstrated that PdNIP2 transporter genes were constitutively expressed in date palm. Silicon aggregates/phytoliths were found in specific stegmata cells present in roots, stems and leaves and their surfaces were composed of pure silica. Stegmata were organised on the outer surface of the sclerenchyma bundles or associated with the sclerenchyma of the vascular bundles. Phylogenetic analysis clustered NIP2 transporters of the Arecaceae in a sister position to those of the Poaceae. It is suggested, that Si uptake in date palm is mediated by a constitutively-expressed Si influx transporter and accumulated as Si aggregates in stegmata cells abundant in the outer surface of the sclerenchyma bundles (fibres).